Influência da textura superficial na indução de vibração por meio de fluxo de ar em sistema piezoelétrico de conversão de energia - Rodrigues, André Luis Gunes (2022)
Piezoelectric Energy Harvesting Systems PZTEH are being used more and more, driven by the development of electronic components called ULP (Ultra Low Power) that demand low energy consumption. This provides the use of energy, previously considered lost. The analysis of vibrational systems with energy conversion by piezoelectric ceramics has been studied and new components developed. This is either in the direct scope of energy conversion with new actuator projects or in the study and development of energy converters, which may act directly with ceramics or their transducer derivatives, with the intention of amplifying the generated energy. Some publications indicate that the use of wind as an inductor or amplifier, in the gain of energy production in a cantilever system exposed to an air flow. Others verified that the physical design interference, analyzing this aerodynamic influence as flutter, galloping effect and vortex, contribute to the amplification of the amplitude of this vibration and, consequently, in the energy generation. The goal of this dissertation is to analyze experimentally and investigative the influence of surface texture on energy gain, by induction and interaction with the wind in a cantilever beam. The drilling of slots, circles holes and surface cavities (same slots and circles figures) will be evaluated in relation to this air interaction (generated turbulence) on the beam, forcing it to vibrate. A piezoelectric transducer, type buzzer (PZT - Titanate Zirconate Lead), will be rigidly attached near the base of the beam, working as an energy transducer. The results obtained showed that the textures applied to the surface of the beams influenced the mechanical properties and the energy generated by each beam. It was concluded that the cantilever beam with lower stiffness and damping is the best choice to be used with systems excited by wind for EH (energy harvesting) produce, and that the texture of surface can be an important factor to increase energy generation.